Inonotus obliquus Polysaccharide Ameliorates Azoxymethane/Dextran Sulfate Sodium-Induced Colitis-Associated Cancer in Mice via Activation of the NLRP3 Inflammasome - Li, Jiawei; Qu, Chao; Li, Fangfang; Chen, Yifang; Zheng, Jinjuan; Xiao, Yao; Jin, Quanxin; Jin, Guihua; Huang, Xuezhu; Jin, Dan (Frontiers in Pharmacology, 2021)
Inonotus obliquus polysaccharide (IOP), the primary constituent of the parasitic fungus I. obliquus, has anti-tumor, anti-inflammatory, anti-oxidation effects. However, the roles of IOP on colitis-associated colorectal cancer (CAC) are still unclear. Herein, we tested the efficacy of IOP using a mouse model of CAC induced by azoxymethane and dextran sulfate sodium (AOM/DSS). We confirmed that intragastric administration of IOP decreased CAC-induced body weight loss, colon tissue damage, colon shortening, and expression of proinflammatory mediators. Meanwhile, IOP treatment increased in expression of the NLRP3 inflammasome, IL-1β, and IL-18 in the colon of CAC mice. Moreover, in vitro, IOP inhibited the proliferation of SW620 colorectal cancer cells. Finally, overexpression of NLRP3 with plasmid transfection could further enhance the activation of NLRP3 inflammasome by IOP. Taken together, these results suggest that IOP suppresses the development of CAC, possibly by activation of the NLRP3 inflammasome, and reveal that IOP may be a therapeutic drug candidate for CAC.